Perlindungan Anak di Industri Esport dalam Pencegahan Ekspoloitasi Digital - Nur Sri Maryam Dm (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The rapid growth of the electronic sports (esports) industry has increased the involvement of children as athletes, streamers, and content creators. However, this development has also created significant risks of digital exploitation that are not yet matched by adequate legal protection. This study aims to analyze the forms of digital exploitation experienced by children in the esports industry and to evaluate the effectiveness of Indonesia's legal framework in providing protection. The research employs a normative legal method using statutory, conceptual, and case approaches. Legal materials were collected through library research and analyzed qualitatively. The findings indicate that digital exploitation of children extends beyond economic exploitation to include the misuse of personal identity and data, excessive digital workloads, and exposure to cyber violence. Furthermore, although Indonesia has established laws on child protection, there are no specific regulations governing children's participation in the esports industry. Therefore, strengthening the regulatory framework is necessary to ensure more effective legal protection for children involved in the digital esports ecosystem.